Laser Applications in Metal Orthodontic Bracket Debonding: A Systematic Review - Patryk Woś; Sylwia Kiryk; Tomasz Dyl; Jan Kiryk; Tomasz Horodniczy; Magdalena Szablińska; Magdalena Aleksandra Dubowik; Wojciech Dobrzyński; Marcin Mikulewicz; Jacek Matys; Maciej Dobrzyński (Applied Sciences)
Objective: The aim of this systematic review was to evaluate the effectiveness and safety of various laser wavelengths for debonding orthodontic metal brackets compared to traditional plier-based methods. The primary outcomes assessed were enamel damage, pulp temperature changes, adhesive remnant index (ARI), and shear bond strength (SBS). Materials and Methods: In September 2024, an electronic search was performed across the PubMed, Web of Science (WoS), and Scopus databases, adhering to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the PICO framework. The initial search yielded 453 records. After eliminating 256 duplicates, 197 unique records were left for screening, which ultimately led to the qualification of 8 articles that met the inclusion criteria for both qualitative and quantitative analyses. The risk of bias in the articles was assessed by two independent reviewers. Results: The included studies demonstrated that laser-assisted debonding generally resulted in less adhesive residue on the enamel surface compared to conventional methods, as evidenced by the reductions in ARI scores reported in two studies. Temperature increases during laser use varied depending on the laser type and power settings. The Nd:YAG (neodymium-yttrium, aluminum, garnet) laser was found to cause significant temperature rises, posing a potential risk to pulp tissue, while the Er:YAG (erbium—yttrium, aluminum, garnet) and Er,Cr:YSGG (erbium, chromium—yttrium, scandium, gallium, garnet) lasers produced only negligible increases in pulp temperature. SBS comparisons revealed no significant differences between the laser-assisted and traditional debonding methods. Additionally, diode lasers demonstrated the potential to minimize enamel damage, particularly when operated at lower power settings. Four publications were assessed as high quality (low risk of bias), and another four as moderate quality (average risk of bias). Conclusions: In conclusion, laser-assisted orthodontic metal bracket debonding, when conducted with appropriately calibrated parameters, is a safe method for preserving tooth tissue. However, its advantages appear to be minimal compared to conventional plier-based methods, highlighting the need for further research to justify its broader clinical application.